Interactive Effects of Drought-Tolerant Varieties and Fertilizer Microdosing on Maize Yield, Nutrients Use Efficiency, and Profitability in the Sub-Humid Region of Benin - Tovihoudji, Pierre G.; Bagri, B. Moukaïla; Batamoussi Hermann, Michel; Tonnang, Z. E. Henri; Akponikpè, P. B. Irénikatché (Frontiers in Agronomy, 2022)
In sub-Saharan Africa, smallholder farming systems continue to record very low yields despite the availability of appropriate crop management technologies. A 2-year field experiment was conducted in 2018 and 2019 at the Agricultural Research Station of Northern Benin to evaluate the growth response, grain yield attributes, and nutrient- and water- use efficiencies of different drought-tolerant (DT) maize varieties (TZEE-W-POP-STR QPM, TZE-Y-POP-STR, 2008Syn-EE-W DT-STR, and 2000Syn-EE-W of 80–90 days cycle), compared to DMR-ESR-W, a drought-susceptible (DS) variety of 90 days cycle, under different fertilizer options [no fertilizer control, microdosing option 1 (MD1, 25 kg N ha−1 + 4 kg P ha−1), option 2 (MD2, 25 kg N ha−1 + 8 kg P ha−1), option 3 (MD3, 35 kg N ha−1 + 8 kg P ha−1), and broadcast fertilizer at recommended rate (RR, 76 kg N ha−1 + 13 kg P ha−1). Generally, combining microdosing with DT varieties showed a very good performance by increasing the leaf area and biomass by 71 and 85%, respectively, at anthesis compared to the conventional practice. Microdosing increases grain and stover yields by 171 and 98%, respectively, compared to an unfertilized control with generally no difference between MD3 and RR treatments. Also, the DT varieties obtained the best yields (+19%), with the highest value observed with the TZE-Y variety. Significant interaction was found between varieties and fertilization for grain and stover yields. During the two cropping seasons, microdose fertilization increases the DT grain yield and gross return by 658 kg ha−1 and 203USD, respectively, than their application on drought sensitive variety. The results of the current study demonstrated that there is a considerable potential for smallholder farmers of northern Benin to improve the maize productivity by means of DT varieties and of fertilizer microdosing. Using, especially, the MD3 option on the DT variety, TZE-Y, may be the best combination in optimizing the maize production in the sub-humid region of Benin, instead of the climate sensitive variety of the DMR-ESR under the microdosing or a common fertilization practice. However, further testing of the technologies through on-farm experiments are required before a precise advice can be given. Precisely, there is a need to evaluate these management options in farmer's fields, taking into account the climatic, soil, and management conditions to better assess and understand the variation in response and in economic benefits and risk.